In Situ Growth of Surfactant-Free Gold Nanoparticles on Nitrogen-Doped Graphene Quantum Dots for Electrochemical Detection of Hydrogen Peroxide in Biological Environments - Ju, Jian; Chen, Wei (Analytical chemistry (Washington), 2015)
In this work, we report a green and simple strategy for the in situ growth of surfactant-free Au nanoparticles (Au NPs) on nitrogen-doped graphene quantum dots (Au NPs–N-GQDs). The formation of hybrid was achieved by just mixing the N-GQDs and HAuCl4·4H2O without addition of any other reductant and surfactant. High-resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) characterizations clearly showed the formation of Au nanoparticles with predominantly exposed (111) facets which can provide more adsorption sites. Such nonsurfactant-capped Au NPs can provide naked catalytic surface with highly electrocatalytic activity. The Au NPs–N-GQDs exhibit high sensitivity and selectivity for electrochemical detection of hydrogen peroxide (H2O2) with a low detection limit of 0.12 μM and sensitivity of 186.22 μA/mM cm2. Importantly, the Au NPs–N-GQDs-based electrochemical biosensor has shown great potential applications for detection of H2O2 levels in human serum samples and that released from human cervical cancer cells with satisfactory results. The present study demonstrates that such novel Au NPs–N-GQDs nanocomposite is promising for fabrication of nonenzymatic H2O2 biosensors.